MiR-338-3p inhibits epithelial-mesenchymal transition in gastric cancer cells by targeting ZEB2 and MACC1/Met/Akt signaling - Huang, Na (Oncotarget, 2015)
MicroRNAs (miRNAs) are involved in the epithelial-mesenchymal transition (EMT) process and are associated with metastasis in gastric cancer (GC). MiR-338-3p has been reported to be aberrantly expressed in GC. In the present study, we show that miR-338-3p inhibited the migration and invasion of GC cells in vitro. Knocking down miR-338-3p in GC cells led to mesenchymal-like changes. MiR-338-3p influenced the expression of the EMT-associated proteins by upregulating the epithelial marker E-cadherin and downregulating the mesenchymal markers, N-cadherin, fibronectin, and vimentin. In terms of mechanism, miR-338-3p directly targeted zinc finger E-box-binding protein 2 (ZEB2) and metastasis-associated in colon cancer-1 (MACC1). MiR-338-3p repressed the Met/Akt pathway after MACC1 inhibition. Reintroduction of ZEB2 and MACC1 reversed miR-338-3p-induced EMT suppression. Consistently, inverse correlations were also observed between the expression of miR-338-3p and ZEB2 or MACC1 in human GC tissue samples. In conclusion, miR-338-3p inhibited the EMT progression in GC cells by targeting ZEB2 and MACC1/Met/Akt signaling.